Peran Guru PAK Dalam Membentuk Moral Dan Karakter Siswa Dilingkungan Pendidikan - Diana Nome; Rupina Rupina; Sandra R. Tapilaha (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
In the world of education, Christian religious education teachers play an important role in shaping the ethics, character and morals of students, because in the world of education most students experience character and moral crisis problems, where they are not controlled by the influence of technological developments and even environmental conditions. can also influence students' ethics, character and morals. Therefore, attention is really needed from various parties, especially the role and attention of teachers in the world of education, in teaching and learning with the aim of helping students learn about the world of education from not knowing to knowing, especially knowing character and morals. Educators not only aim to teach, but educators must also act as teachers who take part in building students' morals and character, and are responsible in accordance with the goals of education and learning to shape and create a generation with noble morals. so that every student has good character and morals in living the days of his life.